Biology and Control of Amazon Sprangletop and Bearded Sprangletop in Florida Rice - Alex C. Rodriguez; Dennis C. Odero (EDIS)
This article describes the biology and control options for sprangletop species associated with rice in Florida to assist growers in making correct identification and appropriate management decisions. Written by Alex C. Rodriguez and D. Calvin Odero, and published by the UF/IFAS Agronomy Department, April 2022.